483 A snapshot of 3887 belgian employee's work-ability: a comparison between age groups. (24th April 2018) - Vandenbroeck, Sofie; Aerts, Liesbeth; Daenen, Liesbeth; Vandersmissen, Lieve; Godderis, Lode
Abstract : Introduction: Working life will increase due to a raise of the legal retirement age. Yet, its success will depend on the willingness and ability of workers to remain at work. Work-ability, the backbone of sustainable employability, should therefore continuously be monitored and promoted. Work-ability is determined by health and functional capacities; competences; values, attitudes and motivation; work, work community and leadership. Evidence shows that health, functional capacities and work (community) affect work-ability the most. Work-ability and both latter factors were therefore assessed in a large sample of employees and compared between younger and older workers. Methods: A cross-sectional study was performed in 100 Belgian companies. The online questionnaire 'Wellfie' was used, which is based on the 'house of work-ability'. The tool consists of validated scales assessing work-ability using four questions of the work-ability index (Range: 1: very bad to 5: very good), lifestyle (diseases) and physical burden. Descriptive statistics were performed using frequencies and equality of proportions was analysed using Chi-square. Result: 3887 participants completed Wellfie (i.e. 67% female, 33% male; 60% age <45, 40% age ≥45). Their current work-ability was similar (Mean: 3.90), yet the predicted work-ability in the upcoming two years was significantly lower in the upper age group (Mean: 4.10 versus 3.95; p<0.05). Employees of 45 years or more reported more musculoskeletal disorders affecting their work (27.7% versus 16.7%), episodes of burnout or depression (17.5% versus 13%; p<0.05) and lifestyle diseases such as diabetes (2.4% versus 1.1; p<0.05), arterial hypertension (25.9% versus 10%; p<0.05) and cardiovascular diseases (10% versus 4.6; p<0.05). The reported amount of physical burden (e.g. repetitive movements, lifting) is comparable between age groups. Discussion: Ageing goes along with a higher risk for chronic diseases and comorbidities affecting employee's work-ability. Employers should therefore invest more in a health promotion policy for all workers.